The impacts of indigenous herbivore grazing over five years (2004 - 2008) on vegetation dynamics in four distinct vegetation types of the winter-rainfall Little Karoo - Madden, Christine (Department of Biological Sciences, 2017)
Vegetation in semi-arid regions is subject to change when heavily utilised by herbivores. Changes in species richness, species and growth form composition, total cover and plant palatability in response to rest (fenced) and grazing (open) treatments was investigated in Sanbona Wildlife Reserve over five years (2004-2008). This reserve is over 55 000 ha and has four dominant vegetation types: Little Karoo Quartz Vygieveld, Western Little Karoo, Montagu Shale Renosterveld and previously transformed Renosterveld classified here as Old Lands. There was no significant change in vegetation dynamics between the fenced or open plots. There were significant differences between years in some vegetation types. All vegetation types showed both treatments having similar shifts in floristic composition. Floristic composition deviated the greatest in 2008 in all vegetation types. This was attributed to an increase in summer and winter rainfall in 2008, as all plots were similarly affected. There was no observed impact of herbivores although disturbance from small rodents and baboons was observed in a few plots. The lack of detectable difference between the fenced and open sites was attributed to low stocking rates, good rainfall and insufficient time.